Model Integrasi Pengelolaan Zakat antara Negara dan Masyarakat Sipil - Hartoyo, Hartoyo (Jurnal Analisis Sosial Politik, 2020)
This study explains the position and authority of community zakat institutions in the management of zakat. Data collected through in-depth interviews and documentation. The results found that the zakat management model according to Law No. 38 of 1999 has substantive limitations in improving people’s welfare. The government is only able to establish BAZ and LAZ, but it lacks guidance and protection. As a result, each zakat institution is left to work in its own space, elitist, performs the same function, and conflicts of interest occur. The passing of Law No. 23 of 2011 is the answer to various legal issues regarding zakat management. The disadvantage is that in addition to having more authority, BAZNAS can also perform LAZ and UPZ functions. This model is still vulnerable to conflicts of interest between zakat managers. The integration model can be a solution while still providing a space of authority to the state while being able to empower the role of civil society. This model is able to optimize the roles of LAZ and UPZ which are under the coordination, protection and guidance of BAZNAS. Penelitian ini menjelaskan posisi dan otoritas lembaga zakat masyarakat dalam pengelolaan zakat. Data dikumpulkan melalui wawancara mendalam dan dokumentasi. Hasil penelitian menemukan bahwa model pengelolaan zakat menurut UU No. 38 Tahun 1999 memiliki keterbatasan substantif dalam meningkatkan kesejahtaraan rakyat. Pemerintah hanya mampu mengukuhkan BAZ dan LAZ, tetapi kurang melakukan pembinaan dan perlindungan. Akibatnya, masing-masing lembaga zakat dibiarkan bekerja dalam ruangnya sendiri, elitis, melakukan fungsi yang sama, dan terjadi konflik kepentingan. Disahkannya UU No. 23 Tahun 2011 merupakan jawaban atas berbagai persoalan hukum tentang pengelolaan zakat. Kelemahannya adalah BAZNAS selain memiliki otoritas lebih juga dapat menjalankan fungsi LAZ dan UPZ. Model ini masih rentan terjadi konflik kepentingan antar pengelola zakat. Model integrasi dapat menjadi solusi dengan tetap memberi ruang otoritas kepada negara sekaligus mampu memberdayakan peran masyarakat sipil. Model ini mampu mengoptimalkan peran LAZ dan UPZ yang berada di bawah koordinasi, perlindungan dan pembinaan BAZNAS.